2012
DOI: 10.1016/j.foodres.2011.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Total carotenoid content, α-carotene and β-carotene, of landrace pumpkins (Cucurbita moschata Duch): A preliminary study

Abstract: Landrace pumpkins occur in nature and their potential as source of pro-vitamin A may be investigated in order to be used in conventional plant breeding or biofortification programs, aiming to increase the total carotenoids and β-carotene contents. The objective of the study was to determine the total carotenoid, α-carotene, β-carotene and its isomers and contents in two landrace samples (A and B) of raw pumpkins (Cucurbita moschata) to verify its seed production potential. High Performance Liquid Chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
149
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(175 citation statements)
references
References 13 publications
10
149
1
15
Order By: Relevance
“…For example, Murkovic et al [4] reported that the α-carotene content of fresh pumpkins ranged from 0 to 7.5 mg/100 g, whereas de Carvalho et al [3] reported that the α-carotene content of landrace pumpkins (Cucurbita moschata Duch) ranged from 67.07 to 72.99 μg/g. In the present study, the most abundant carotenoid found in fresh pumpkin samples was α-carotene, the content of which was 386.22 μg/g DW, accounting for nearly 50% of the total carotenoid content.…”
Section: Degradation Kinetics Of α-Carotenementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Murkovic et al [4] reported that the α-carotene content of fresh pumpkins ranged from 0 to 7.5 mg/100 g, whereas de Carvalho et al [3] reported that the α-carotene content of landrace pumpkins (Cucurbita moschata Duch) ranged from 67.07 to 72.99 μg/g. In the present study, the most abundant carotenoid found in fresh pumpkin samples was α-carotene, the content of which was 386.22 μg/g DW, accounting for nearly 50% of the total carotenoid content.…”
Section: Degradation Kinetics Of α-Carotenementioning
confidence: 99%
“…[1] The reddish yellow colour of pumpkin solely depends on the varieties and contents of carotenoids, and the main carotenoids present in pumpkin include β-carotene (more than 80% of the total carotenoid content), α-carotene and a few xanthophylls. [2][3][4] Carotenoids in the diet are mostly associated with the beneficial effects on human health. Several studies have indicated that carotenoid intake may reduce the risk of certain types of cancer, degenerative and cardiovascular diseases, cataracts and macular degeneration, which plays an important role in disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The total phenolic contents were expressed as mg of Gallic Acid Equivalent (GAE) per 100 g. Total flavonoids content present in the selected by-products were estimated by the aluminum chloride colorimetric assay as described by Marinova et al, (2005). The total flavonoids contents were expressed in mg Quercetin equivalent (QE) per 100 g. Tannin content was measured using Folin-Denis method described by Sadasivam and Manickam (2008) and results were expressed as mg of Tannic Acid Equivalent (TAE) per 100 g. The total carotenoid content was spectrophotometrically determined as per the method described by (Lucia et al, 2012). The DPPH assay was performed as described by Lim et al, (2007) with slight modifications.…”
Section: Determination Of Total Polyphenolics Flavonoids Carotenoidmentioning
confidence: 99%
“…32 Some screenings have used landraces from secondary centres of diversity, such as Brazil and Malaysia, and have found high levels of variation for these traits in landraces from different areas. [33][34][35] Further studies will be conducted with the set of collected accessions to evaluate their carotenoid content. Accessions with high carotenoid contents may be utilised for further quality improvement of pumpkin during the development of new varieties, which will contribute to minimising nutritional problems in the population, especially those arising from vitamin A deficiency in children and women.…”
Section: Genetic Diversity Of Cucurbita Speciesmentioning
confidence: 99%